The Authority of Bale Mediasi in the Settlement of Criminal Cases in West Nusa Tenggara Province (A Deliberative Approach) - Nurmadiah, Geatriana (Journal of Transcendental Law, 2024)
The settlement of criminal cases is the authority of law enforcement, in this case the police, prosecutors, and courts. In criminal law, penal mediation or diversion is also known, but the mediator is usually a law enforcement officer and is completed in law enforcement institutions, not in certain communities such as the West Nusa Tenggara Bale Mediasi. The research method used in this research is normative research with a statute approach and conceptual approach. The results of the research found that Bale Mediasi has the authority to resolve criminal cases as long as it does not conflict with statutory regulations, based on the spirit of restorative justice and diversion in Law Number 11/2012, local values, and handling cases through consensus procedures. So that an agreement between the parties is reached as referred to in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. The deed of peace in criminal cases produced through the mediation process at Bale Mediasi is final and binding. To strengthen the peace deed, it can be registered with the court to obtain executorial power. If no peace agreement is reached between the parties, the dispute settlement continues in accordance with applicable legal procedures in a professional and proportional manner. It is suggested that it needs to be clarified in regional regulation number 9 of 2019 concerning Bale Mediasi related to the type of religious civil disputes that can also be obtained to the religious court to obtain executorial power. In addition, it is necessary to hasten the signing of a memorandum of understanding between the Governor and the Head of the Regional Police, the High Prosecutor and the President of the High Court as the basis for the executorial deed of peace.